The Emergence of Climate Litigation in the Global South. (2020) - Lin, Jolene
Abstract : Climate litigation in the Global South tends to be couched in rights-based clams including the right to life and a clean and healthy environment. Jolene Lin explained that this is in part due to the fact that many jurisdictions in the Global South have embedded environmental rights in their constitutions and, in some cases, courts have interpreted the right to life to include the right to a clean and healthy environment.